Management of Chronic Exertional Compartment Syndrome and Fascial Hernias in the Anterior Lower Leg With the Forefoot Rise Test and Limited Fasciotomy. (March 2014) - Finestone, Aharon S.; Noff, Matityahu; Nassar, Yussuf; Moshe, Shlomo; Agar, Gabriel; Tamir, Eran
Background: Chronic exertional compartment syndrome can present either as anterolateral lower leg pain or as painful muscle herniation. If an athlete or a soldier wants to continue training, there is no proven effective nonoperative treatment, and fasciotomy of 1 or more of the lower leg muscle compartments is usually recommended. Our clinical protocol differs from most reported ones in the use of the forefoot rise test to increase pressure and provoke pain and our recommending minimal surgery of the anterior compartment only. We present results of surgery based on our clinical management flowchart. Methods: Patients who had surgery during a 12-year period were reviewed by telephone interview or office examination. Pain was graded from 0 (none) to 4 (unbearable). Preoperative resting and exercise anterior compartment pressures were evaluated in most subjects before and immediately following a repeated weight-bearing forefoot rise test. Surgery was under local anesthesia, limited to the anterior compartment only and percutaneous (excepting muscle hernias). There were 36 patients, mean age 24 years. Results: Of 16 patients who were originally operated unilaterally, 5 patients were later operated on the other side. Mean presurgery resting pressure was 56 mm Hg (40-80 mm Hg) rising to 87 mm Hg (55-150 mm Hg) with exercise. Mean exercise pain score dropped from 2.9 presurgery to 1.3 postsurgery (n = 35, P < .0001). Complications included superficial peroneal nerve injury (3 legs in 3 patients, 1 requiring reoperation). Conclusion: When we used our clinical management flowchart based on the forefoot rise test, percutaneous fasciotomy of the anterior compartment alone provided good clinical results. Care must be taken to prevent injury to the superficial peroneal nerve in the distal lower leg. Level of Evidence: Level IV, retrospective case series.